(untitled) (Bangladesh Journal of Neuroscience, 2017)
Background: Alzheimer’s disease is the most common cause of dementia. Metals such as zinc , copper, iron are likely involved in the neurodegeneration of Alzheimer’s disease . Copper can catalyze a flux of reactive oxygen species that can damage functional and structural macromolecules in brain. Most studies found association of high serum copper level with Alzheimer’s disease but also some studies did not. Methods: Total 48 patients of Alzheimer’s disease who were diagnosed according to NIA-AA ( National institute of Aging – Alzheimer’s Association) recommendation ( revised NINCDS-ADRDA) criteria were taken as study population purposively and 42 age and sex matched control were selected. Fasting serum copper level were done for both groups. Comparison of serum copper level of Alzheimer’s patients with that of the control group were done to see association. Results : A total of 28 male and 20 female with mean age of 66.20 ± 9.42 (mean±SD) years, 22 male and 20 female with mean age of 63.54 ± 9.74 (mean±SD) years constituted as case and control groups, respectively. The mean of serum copper in case and control groups were 0.95 ± 0.37 versus 0.92 ± 0.25 mg/L (P > 0.05). The present study found that serum copper levels are non-significantly higher in patients with AD than control group, however it did not show a significant relationship with severity of dementia. Conclusion: So our suggestion was to perform a study work including total serum copper level , serum ceruloplasmin level and free serum copper level comparing between a large Alzheimer’s Disease patients group and age , sex matched apparently healthy control group to understand the copper dyshomeostasis in Alzheimer’ Disease. Bangladesh Journal of Neuroscience 2017; Vol. 33 (2): 96-102